(9x+44=6x+3)77

Simple and best practice solution for (9x+44=6x+3)77 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x+44=6x+3)77 equation:



(9x+44=6x+3)77
We move all terms to the left:
(9x+44-(6x+3)77)=0
We calculate terms in parentheses: +(9x+44-(6x+3)77), so:
9x+44-(6x+3)77
determiningTheFunctionDomain 9x-(6x+3)77+44
We multiply parentheses
9x-462x-231+44
We add all the numbers together, and all the variables
-453x-187
Back to the equation:
+(-453x-187)
We get rid of parentheses
-453x-187=0
We move all terms containing x to the left, all other terms to the right
-453x=187
x=187/-453
x=-187/453

See similar equations:

| 10-4-3w=-w-10 | | 2+x/28=6 | | 6x+36=24 | | Y+3=2(x+7) | | 2p-(1-p)=-3 | | 12x+7+5x-1=180 | | c/4+8=10 | | 10-3b=-5(b-5)+2b | | p−5×3=−20 | | z-0.2z+4.8=1.6(2-0.5) | | 12x+7+5x-1=108 | | 0.55+0.05(16-x)=0.10(98) | | -(x-3)+6=6+3(x+1) | | -5+6d-21=-5 | | 3a-4(a-5)=1 | | y/3+5=-14 | | 6=x9-9 | | 42-5x=4x+15 | | 5=u/2-5 | | -20=4+4x | | (-5,6)m=2/3 | | 25×9=4m | | -.5(t+9)+23/4t=3/8t | | 4m=25×9 | | 3x^2=160 | | y-4y+3=5(y+3.4) | | 6-3x=6-3x | | 25m=9-4 | | 7c+4=2+8c | | -x^-4x=21 | | 3x+13=6x-3 | | 2.7x+42.8=11.4-13.0x |

Equations solver categories